Intensifikasi Pajak Restoran oleh Badan Keuangan Daerah (BAKEUDA) Kota Tegal Tahun 2021-2023 - Amanda Alifia Pridianty; Mas Rasmini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research analyzes the restaurant tax intensification activities conducted by the Regional Financial Agency (Badan Keuangan Daerah, Bakeuda) of Tegal City from 2021 to 2023, with the aim of increasing restaurant tax revenue. Data collection was carried out through interviews, observations, and document studies. This research using a qualitative descriptive research method. The research findings identify six intensification efforts in accordance with (Kustiawan, 2019) implemented by Bakeuda: (1) organizational restructuring, (2) digitalization of the tax administration system, (3) installation of transaction recording devices (tapping box), (4) establishment of an integrated cross-organization team, (5) training and education for human resources, and (6) socialization of tax obligations. Although the intensification efforts have been successful, challenges related to awareness and perception persist. The study also encountered significant obstacles, including low public tax awareness, negative perceptions regarding the audit process, and difficulties in accessing tax information for small businesses. Recommendations include optimizing socialization through digital media and improving the information system to encourage tax compliance and contributions to regional development.